2022
DOI: 10.1002/agm2.12217
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal on mitochondrial dysfunction in Alzheimer’s disease

Abstract: It is widely recognized that Alzheimer's disease (AD) is a common type of progressive neurodegenerative disorder that results in cognitive impairment over time. Approximately 152 million cases of AD are predicted to be reported by 2050. Amyloid plaques and tau proteins are two major hallmarks of AD which can be seen under electron microscope. Mitochondria plays a vital role in the pathogenesis of AD and mitochondria disruption leads to mitochondrial DNA (mtDNA) dysfunction, alteration of mitochondria dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
(227 reference statements)
0
10
0
Order By: Relevance
“…Dementia, which includes AD, affects 50 million individuals globally, most of whom are senile. According to the World Health Organization (WHO), AD is the world's fifth leading cause of death, with the number of fatalities anticipated to triple by 2050 if current trends continue 2 . AD is diagnosed using brain imaging, physical and cognitive evaluations, laboratory tests, and medical history 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dementia, which includes AD, affects 50 million individuals globally, most of whom are senile. According to the World Health Organization (WHO), AD is the world's fifth leading cause of death, with the number of fatalities anticipated to triple by 2050 if current trends continue 2 . AD is diagnosed using brain imaging, physical and cognitive evaluations, laboratory tests, and medical history 3 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), AD is the world's fifth leading cause of death, with the number of fatalities anticipated to triple by 2050 if current trends continue. 2 AD is diagnosed using brain imaging, physical and cognitive evaluations, laboratory tests, and medical history. 3 The risk factors for AD include apolipoprotein E4 (APOE4) genotype and traumatic brain injury, family history and age, obesity, diabetes, hypercholesterolemia, hypertension, and a lack of education.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…Neurodegenerative disorders are conditions in which the central nervous system cells stop functioning or die [ 51 , 52 , 53 ]. The majority of neurodegenerative diseases are incurable and often worsen with time [ 54 , 55 ].…”
Section: Depression As a Neurodegenerative Disordermentioning
confidence: 99%